An analysis on the relationship between ESG information disclosure and enterprise value: A case of listed companies in the energy industry in China - Dong Siwei; Wongvanichtawee Chalermkiat (Cogent Business & Management)
This study examines the relationship between environment, social responsibility, and governance (ESG) information disclosure and firms’ value. It also investigates how debt cost is the mediate variable between the ESG and firms’ value. The content analysis supported sustainability development theory, stakeholder theory, and the double carbon target in China. The multiple linear regression is used to examine the relationships for a sample of 94 firm 4-year observations listed in the GICS energy industry during 2018–2021 in China. The results show that ESG is significantly positively associated with firms’ value. Nevertheless, debt cost is negatively and significantly related to ESG. More importantly, the results show that debt cost mediates ESG firms’ value relationship. Further, when the sample is split into state-owned and non-state-owned firms, the ESG- firms’ value significant positive relationship is evident only in the latter, corroborating the mediate role of the debt cost in China. This study contributes to the literature on ESG, debt cost, and firms’ value by offering evidence for the mediating role of debt cost on the ESG firms’ value relationship, supporting the view that non-state-owned firms are more sensitive. Regulators and stakeholders should be aware of the potential effect of engagement in ESG reporting and the benefits of having a low cost of debt on firms’ value.